Chronology of COVID-19 Cases on the Diamond Princess Cruise Ship and Ethical Considerations: A Report From Japan - Nakazawa, Eisuke; Ino, Hiroyasu; Akabayashi, Akira (Disaster medicine and public health preparedness, 2020)
The Diamond Princess cruise ship has been anchored at the Yokohama port in Japan since February 3, 2020. A total of 691 cases of the coronavirus disease 2019 (COVID-19) infection had been confirmed as of February 23. The government initially assumed that the infection was not spreading aboard and therefore indicated that any persons who either tested negative for the virus or were asymptomatic should immediately disembark. However, on February 5, the government set a 14-day health observation period because of the severity of the infection. Passengers confirmed to be free from infection began disembarking on Day 15 (February 19) of the quarantine. The effectiveness and validity of infection control, justification for the timing of inspections, and even the nature of COVID-19 itself now are all in question. The ethical considerations related to cruise ship infection control include the reasonable justification for isolation, the psychological fragility and quality of life of the isolated passengers and crew members, the procedural justice inherent in a forced quarantine, and the optimization of control measures. The international coordination framework and the global ramifications of such outbreaks should be reevaluated by the international community. Denying a ship’s entry based on local politics is incompatible with global justice. Events such as these require an international response and global regulations that seek to reduce disparities.